Role played by T-helper 2 in resetting the cytokine balance in allergic patients - Mohamed Y Attia; Howida M Saber (SpringerOpen, 2014)
Background Bronchial asthma is an allergic disorder characterized by excessive hyperactive nature of the airways, which depends on many cytokines such as interleukin-4 (IL-4) and IL-5 that are responsible for the allergic inflammatory response. One of the strategies in the management of bronchial asthma is the induction of synthesis of IL-10; it has an inhibitory effect on the synthesis of the T-helper-2 (Th2) cytokines. Th2 cells play a triggering role in the activation/recruitment of immunoglobulin E antibody-producing B cells, mast cells, and eosinophil cells. To assess regulatory changes in the immune system, in patients with allergy and asthma, we studied the cytokine profile in serum in comparison with normal healthy controls. The study was carried out in Allergy and Immunology Unit, Ain Shams University Hospitals. A total of 170 patients with various allergies and asthmatic conditions were studied, for cytokines in the serum by enzyme-linked immunosorbent assay using kits from Immune Technology, and analyzed to identify the triggering factors or main contributors toward allergy and asthma. Our study showed increase in the levels of IL-4, IL-5, and IL-6 in all groups, which was nonsignificant. However, the levels of IL-10, IL-13, and tumor necrosis factor-α were highly significantly increased. Besides, we found correlation of granulocyte macrophage colony-stimulating factor with IL-10. Significant positive correlation with different cytokines was observed. Most of these patients showed increase in immunoglobulin E levels. This study gives a better understanding of how cytokines are the mediators of balance of Th1 and Th2 immune responses and how immunoglobulin E synthesis is controlled by cytokines. Further studies will eventually lead to improved treatment strategies in the clinical management of immunoglobulin E-mediated allergy.